The Influence of Market Prices, Income, and Tastes on Demand for Fashion Products in the Virtual Market on the Shopee Application - Juliani Pudjowati; Susi Tri Wahyuni; Siti Nurul Asyiyah; Mas’adah Mas’adah (Institute of Computer Science (IOCS), 2023)
This study aims to find out